Regards croisés entre le droit innu et le droit québécois : territorialités en conflit - Motard, Geneviève (McGill Law Journal / Revue de droit de McGill, 2020)
This article presents a study of the main characteristics (actors, values, principles, and rules) of the Quebec and Innu legal traditions with respect to their relationship to territory. This primarily descriptive study is followed by an analysis of the interactions that govern the two legal traditions. The article highlights the process of invalidation of the rules of Indigenous law effectuated by Quebec’s law of public and private property, and land resources more generally.